Clinician and Patient Characteristics Associated With Lung Cancer Screening Following a Shared Decision-making Visit - Goodwin, James S. (JAMA Netw Open, 2020)
This cohort study explores whether clinician specialty and patient familiarity with the attending clinician are associated with rates of low-dose computerized tomographic lung cancer screening after shared decision-making visits.